2006
DOI: 10.1124/jpet.106.114181
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick C1-Like 1 Overexpression Facilitates Ezetimibe-Sensitive Cholesterol and β-Sitosterol Uptake in CaCo-2 Cells

Abstract: Previous in vivo studies including those with knockout mice suggested that Niemann-Pick C1-like 1 (NPC1L1) plays an essential role in the intestinal absorption of cholesterol. To characterize the mechanism of cholesterol uptake mediated by NPC1L1, an in vitro system reflecting the function of this transporter needs to be established. In the present study, we constructed NPC1L1 overexpressing CaCo-2 cells as an in vitro model and characterized the transport properties of NPC1L1. Immunohistochemical staining rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 20 publications
(29 reference statements)
6
108
3
2
Order By: Relevance
“…As we described, it was reported that NPC1L1 was identified as a critical factor for cholesterol absorption. 14) We then next determined the effects of various concentrations of ezetimibe on uptake of cholesterol by Caco-2 cells (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we described, it was reported that NPC1L1 was identified as a critical factor for cholesterol absorption. 14) We then next determined the effects of various concentrations of ezetimibe on uptake of cholesterol by Caco-2 cells (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…This result is roughly consistent with previous reports. 14,15) We set that ezetimibe at a concentration of 25 µM inhibited the uptake of a substrate of NPC1L1. We also assessed the presence of NPC1L1 in Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] It is also the molecule target for the new cholesterol-lowering agent, ezetimibe. 9 Human NPC1L1 is expressed mainly in the intestine and liver and is responsible for transporting cholesterol from intestinal lumen to enterocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, although EZE-sensitive cholesterol transport correlates well with the amount of NPC1L1 expression (7,8), it is not possible to determine whether NPC1L1 functions alone or as part of a multiprotein complex [SR-B1 (9-15), CD36 (14), CD13 (9), caveolin-1/annexin-2 (16)], facilitating the transfer of cholesterol from outside the cell to internal cholesterol pools (9,15). Furthermore, it has been speculated that EZE may inhibit cholesterol transfer by binding to some of these other targets, in addition to its inhibition of NPC1L1 (9).…”
mentioning
confidence: 99%